Decoding high Gonadotropin-releasing hormone pulsatility: a role for GnRH receptor coupling to the cAMP pathway? - Cohen-Tannoudji, Joelle; Avet, Charlotte; Garrel, Ghislaine; Counis, raymond; Simon, Violaine (Frontiers in Endocrinology, 2012)
The GnRH pulsatile pattern is critical for appropriate regulation of gonadotrope activity but only little is known about the signaling mechanisms by which gonadotrope cells decode such pulsatile pattern. Here, we review recent lines of evidence showing that the GnRH receptor (GnRH-R) activates the cAMP pathway in gonadotrope cells, thus ending a long lasting controversy. Interestingly, coupling of GnRH-R to the cAMP pathway as well as induction of nitric oxide synthase 1 (NOS1) or follistatin through this signaling pathway take place preferentially under high GnRH pulsatility. The preovulatory surge of GnRH in vivo is indeed associated with an important increase of pituitary cAMP and NOS1 expression levels, both being markedly inhibited by treatment with a GnRH antagonist. Altogether, this suggests that due to its atypical structure and desensitization properties, the GnRH-R may continue to signal through the cAMP pathway under conditions inducing desensitization for most other receptors. Such a mechanism may contribute to decode high GnRH pulsatile pattern and enable gonadotrope cell plasticity during the estrus cycle.